COMPARISON OF NEBULIZED EPINEPHRINE AND NEBULIZED SALBUTAMOL IN CHILDREN HOSPITALIZED WITH ACUTE BRONCHIOLITIS - SAIRA MAHMOOD, JAMAL ANWAR, SHAISTA HAIDER, AZMATULLAH, AREEB SAJJAD (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Acute bronchiolitis is a leading cause of hospitalization in infants, yet the optimal choice of bronchodilator remains debated. This study compared the effects of nebulized epinephrine versus salbutamol on clinical recovery and hospital stay duration. Methods: This randomized controlled trial was conducted at Department of Pediatric Medicine, Sheikh Zayed Hospital, Rahim Yar Khan during October 2024 and March 2025. A clinical analysis was conducted on 60 children with moderate acute bronchiolitis, equally randomized to receive nebulized epinephrine (n=30) or salbutamol (n=30). The primary outcome was length of hospitalization. The secondary outcome was clinical improvement, measured by change in Respiratory Distress Assessment Instrument (RDAI) scores. Due to non-normal data distribution, non-parametric tests (Wilcoxon Signed-Rank, Mann-Whitney U) were used for analysis. Correlational and regression analyses explored demographic influences. Results: Both treatments produced statistically significant reductions in RDAI scores (p < 0.001 for both groups). However, no statistically significant difference was found between groups in the magnitude of clinical improvement (p = 0.129) or hospital stay duration (median 3.0 vs. 3.5 days, p = 0.693). A significant negative correlation was observed between clinical improvement and length of stay (r = -0.353, p < 0.01). Patient age, weight, gender, and symptom duration showed no significant association with treatment response. Conclusion: Nebulized epinephrine and salbutamol demonstrate comparable efficacy in reducing respiratory distress and length of hospitalization in children with acute bronchiolitis. The choice between agents may therefore depend on factors such as cost, availability, and side-effect profile rather than superior effectiveness. These findings support current clinical guidelines that consider both medications as viable options for symptomatic management.